2016
DOI: 10.1111/1477-8947.12104
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability assessment of three districts in the city of Donostia through the NEST simulation tool

Abstract: Nowadays, urbanists are facing increasing demands regarding the performance of urban development projects in terms of environment, quality of life and socio‐economic issues. In order to address these increasing demands, actors involved in urban development projects need tools capable of assessing their impacts. These tools should also enable the comparison of all potential scenarios. Taking into account these needs, Nobatek and Tecnalia have developed NEST (Neighbourhood Evaluation for Sustainable Territories)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 19 publications
0
10
0
2
Order By: Relevance
“…This district is selected for being a representative district of the city in which different buildings with a mix of uses within the ground floors (commercial, garages and small industries) are being gradually replaced by new residential buildings. Most of the information required for modeling the baseline scenario of Gros has been obtained in close collaboration with the municipality of Donostia-San Sebastian and based on assumptions from previous studies [57], as shown in Table 8. Regarding the buildings' information, such as: the energy rating, heating system or heritage protection level, Table 9 shows the main characteristics required as inputs for simulating the use case, i.e., HFA, useful roof or opening and opaque faςade surface.…”
Section: Gros District Case Study Definitionmentioning
confidence: 99%
“…This district is selected for being a representative district of the city in which different buildings with a mix of uses within the ground floors (commercial, garages and small industries) are being gradually replaced by new residential buildings. Most of the information required for modeling the baseline scenario of Gros has been obtained in close collaboration with the municipality of Donostia-San Sebastian and based on assumptions from previous studies [57], as shown in Table 8. Regarding the buildings' information, such as: the energy rating, heating system or heritage protection level, Table 9 shows the main characteristics required as inputs for simulating the use case, i.e., HFA, useful roof or opening and opaque faςade surface.…”
Section: Gros District Case Study Definitionmentioning
confidence: 99%
“…Screenshot of the Gros district case study. The modelization and the environmental assessment has been carried out by NEST tool [12].…”
Section: Gros District Case Study Definitionmentioning
confidence: 99%
“…Some of this data is based on assumptions from previous studies [12]. Table 2 shows the main characteristics of Gros district regarding the relationship between the energy certification of the buildings, their Energy Demand (ED), the quantity of buildings, the Heated Floor Area (HFA) and the amount of surface per building typology.…”
Section: Gros District Case Study Definitionmentioning
confidence: 99%
“…), (II) life cycle inventory, (III) life cycle assessment, and (IV) interpretation [19]. To evaluate the impacts of buildings and cities with an LCA focus, various digital tools have been developed, among which we highlight the Neighbourhood Evaluation for Sustainable Territories (NEST) software [24]. It considers the impact of different stages of the life cycle associated to different processes of the urban environment, including transportation or public lighting.…”
Section: Introductionmentioning
confidence: 99%
“…It considers the impact of different stages of the life cycle associated to different processes of the urban environment, including transportation or public lighting. Thus, in comparison to other tools, NEST takes into account building energy but also energy transportation, energy water, energy public lighting, solid waste, and socioeconomic impacts of the building environment on the district or city studied [24,25]. It is worthy to underline that it is an agile and fast tool for carrying out analysis of the baseline scenario and the improvement hypotheses.…”
Section: Introductionmentioning
confidence: 99%